Changes in STIM isoforms expression and gender-specific alterations in Orai expression in human heart failure - Čendula, R; Dragún, M; Gažová, A; Kyselovič, J; Hulman, M; Máťuš, M (Physiological research, 2019)
Store-operated calcium entry (SOCE) is one of regulatory mechanisms which regulates Ca2+ cycling in the heart. SOCE alterations in pathological conditions contribute to progression of heart failure and cardiac hypertrophy by multiple signaling pathways such as Cn/NFAT and CaMKII/MEF2. Several components mediating SOCE have been identified, such as STIM and Orai. Different isoforms of both Orai and STIM have been detected in animal studies, exhibiting distinct functional properties. This study is focused on the analysis of STIM and Orai isoforms expression in the end-stage human failing myocardium. Left ventricle samples isolated from 43 explanted hearts from patients undergoing heart transplant and from 5 healthy donor hearts were used to determine the mRNA levels of Orai1, Orai2 and Orai3, STIM1, STIM2 and STIM2.1 by qRT-PCR. The expression was further analyzed for connection with gender, related co-morbidities, pathoetiology, clinical data and biochemical parameters. We show that Orai1 expression is decreased by 30 % in failing myocardium, even though we detected no significant changes in expression of Orai2 or Orai3. Interestingly, this decrease in Orai1 was gender-specific and was present only in men, with no change in women. The ratio Orai1/Orai3 was significantly lower in males as well. The novel STIM2.1 isoform was detected both in healthy and failing human myocardium. In the end-stage heart failure, the expression of STIM2.1 was significantly decreased. The lower ratio of STIM2.1/STIM2 in failing hearts indicates a switch from SOCE-inhibiting STIM2.1 isoform to stimulatory STIM2.2. STIM1 mRNA levels were not significantly changed. These observed alterations in Orai and STIM expression were independent of functional heart parameters, clinical or biochemical patient characteristics. These results provide detailed insight into the alterations of SOCE regulation in human failing myocardium. Gender-specific change in Orai1 expression might represent a possible mechanism of cardioprotective effects of estrogens. The switch from STIM2.1 to STIM2.2 indicates an amplification of SOCE and could contribute to the hypertrophy development in the filing heart.
Keywords: dospělí; Female; Stromal Interaction Molecules; Calcium Release Activated Calcium Channels; Adult; ženské pohlaví; Heart Failure; lidé; srdeční selhání; studie případů a kontrol; kanály aktivované uvolněním vápníku; Ventricular Remodeling; Sex Characteristics; proteiny STIM; Male; Case-Control Studies; Protein Isoforms; pohlavní dimorfismus; remodelace komor; lidé středního věku; protein - isoformy; mužské pohlaví; Myocardium; myokard; Middle Aged; Humans